2019
DOI: 10.1007/s13364-019-00433-6
|View full text |Cite|
|
Sign up to set email alerts
|

Polish suture zone as the goblet of truth in post-glacial history of mammals in Europe

Abstract: Present-day species distribution and patterns of genetic diversity in Europe are a result of post-glacial re-colonization from glacial refugia after the Last Glacial Maximum. This process led to the formation of secondary contact zones (suture zones) between the haplogroups of different species, and were induced by several factors, including climate and evolutionary processes like selection and adaptation. One such suture zone has been found in Poland, where a complex network of different phylogenetic lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 112 publications
(169 reference statements)
3
7
0
Order By: Relevance
“…2) are likely reflective of a more widespread and connected populations occupying the Balkans and Carpathian regions during the LGM (as is known from the fossil records; (5)) and a subsequent expansion into the rest of central Europe in the post-glacial period. A similar scenario has been proposed for other large mammals (10,44). At K = 7, French, Belgian and Swiss individuals were grouped with other central European populations but population-level analyses (DAPC and TREEMIX) showed that these populations were distinct from other populations in close proximity (and they formed their own cluster at K = 9 in the individual-based Bayesian analysis; Fig.…”
Section: Phylogeographic Structure Of the Red Fox In Europesupporting
confidence: 75%
“…2) are likely reflective of a more widespread and connected populations occupying the Balkans and Carpathian regions during the LGM (as is known from the fossil records; (5)) and a subsequent expansion into the rest of central Europe in the post-glacial period. A similar scenario has been proposed for other large mammals (10,44). At K = 7, French, Belgian and Swiss individuals were grouped with other central European populations but population-level analyses (DAPC and TREEMIX) showed that these populations were distinct from other populations in close proximity (and they formed their own cluster at K = 9 in the individual-based Bayesian analysis; Fig.…”
Section: Phylogeographic Structure Of the Red Fox In Europesupporting
confidence: 75%
“…The contact zones of different genetic lineages in Central and Eastern Europe were identified for several other mammalian species and they testify to the origin of those lineages from different refugia (e.g. 32 34 ). According to fossil records 35 , during the LGM wild boar inhabited Northern Spain, Central Portugal, Southern France, South-central and North-western Italy, Slovenia, Croatia, and Greece.…”
Section: Discussionmentioning
confidence: 92%
“…These two groups were found to be separated by the River Vistula, indicating limited movements of the host species (e.g., the red fox) across the river. According to Stojak and Tarnowska [ 71 ], however, the contemporary genetic structure of small mammals in Poland indicates that the Vistula could not be an important barrier to gene flow. It seems that the factors enabling red foxes to cross the Vistula are the low water levels often recorded in summer (in some stretches it can be as shallow as ca 40 cm) and the numerous sandy islands in the riverbed.…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned earlier, female red foxes occupy home ranges or territories while the males are migratory. We do not believe that the River Vistula was a barrier to the effective flow of maternal genes (it was shown by the Mantel test and suggested by Stojak and Tarnowska [ 71 ]).…”
Section: Discussionmentioning
confidence: 99%